INTEGRASI LITERASI DIGITAL: STRATEGI MENINGKATKAN KREATIVITAS MENULIS DAN MENDONGENG MELALUI PROGRAM GENDIS SEWU DI KOTA SURABAYA - M. Amin; She Fira Azka Arifin; Evi Qurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of digital literacy in enhancing writing and storytelling skills among participants of the Gendis Sewu program in Rungkut District, Surabaya. The research employs a qualitative case study approach, using primary data collected through observation, interviews, and documentation. Data analysis used pattern matching, explanation building, and time-series analysis techniques. The results reveal that the digital literacy initiative supported by the Surabaya City Library and Archives Office utilizes the Taman Kalimas platform. The Gendis Sewu program, which includes writing and storytelling classes, has significantly improved participants' abilities to gather information, express ideas, and produce works such as e-books and storytelling videos. This study highlights the effectiveness of integrating digital literacy into educational activities and recommends broader implementation in similar contexts. Keywords: Digital literacy, Writing creativity and storytelling, Gendis Sewu